4CPS-021 Effectiveness, persistence, and adherence of baricitinib in rheumatoid arthritis: long-term real-world evidence study. Issue 1 (23rd March 2023) - Calvo García, A; Ramirez Herraiz, E; Llorente Cubas, I; Varas de Dios, B; Morell Baladrón, A; Benedí González, J; García de Vicuña, R
Abstract : Background and Importance: Baricitinib (BAR) is a Janus kinase inhibitor (JAKi) selective for isoenzymes 1 and 2. It is used in rheumatoid arthritis (RA) with an inadequate response to conventional synthetic disease-modifying drugs (csDMARD). Aim and Objectives: The objective was to evaluate the effectiveness, persistence, and adherence of BAR in RA in a real-world setting. Material and Methods: An ambispective observational study was designed in a third-level hospital. Patients with RA who started BAR between September 2017 and June 2021 were included and signed an informed consent. Patients participating in a clinical trial were excluded. Patients were followed up until December 2021. Effectiveness was evaluated by variation of the Disease Activity Score (28-joint count) using C-reactive protein (DAS28PCR); and by the percentage of patients achieving therapeutic target: low disease activity (LDA) (DAS28CRP≤3.2) or disease remission (DAS28CRP<2.6). Adherence was analysed using the 5 items Compliance-Questionnaire-Rheumatology (CQR5) applied to patients every 6 months, and the medication possession ratio (MPR). The study was approved by the Institutional Review Board of the hospital. Results: 61 patients were included, 51/61 (83.6%) were female. The mean age was 58.1 (15.4) and the mean disease duration was 13.9 (8.3) years. 47/61 (77.0%) and 43/61 (70.5%) patients presented anti-citrullinated protein antibodies and rheumatoid factor, respectively. 44/61 (72.1%) patients had prior exposure to biologic DMARDs. 10/61 (16.4%) patients were on BAR monotherapy. A significant decrease was observed in DAS28PCR from baseline to the end of treatment/follow-up (3.9 (0.9) vs 2.7 (1.3), a difference of 1.2, p=0.000). In addition, 6/61 (9.8%) and 37/61 (60.7%) patients achieved LDA or remission, respectively. 31/61 (50.8%) patients remained on treatment at the end of follow-up, with a median persistence of 31.3 (14.1-47.7) months. The mean MPR was 0.96 (0.08), and all but one patient were adherent (MPR>0, 8). According to the CQR5, all patients were 'good adherers'. Conclusion and Relevance: JAKi are the most recent alternative available for RA treatment. BAR demonstrated effectiveness in our study cohort, with a significant decrease in DAS28PCR, a high percentage of patients reaching the therapeutic target, and a persistence exceeding two years. Adherence to treatment was very high, almost 100%. More studies in real-world setting are needed to confirm these results. References and/or Acknowledgements: Conflict of Interest: No conflict of interest